Living with a transplanted liver is associated with cytopenias: a nationwide cohort study - Kajinth Manogarathaas; Nicoline S. Arentoft; Jens G. Hillingsø; Anne Marie R. Jensen; Annette D. Fialla; Gerda E. Villadsen; Peter Holland-Fischer; Shoaib Afzal; Shoaib Afzal; Børge G. Nordestgaard; Børge G. Nordestgaard; Peter Brown; et al. (Frontiers in Gastroenterology)
Hematological abnormalities are common in liver transplant recipients, but evidence beyond the first-year post-transplantation is scarce. We aimed to evaluate hematological abnormalities in liver transplant recipients beyond the first-year post-transplantation. We included 437 liver transplant recipients and 1,744 age- and sex-matched controls from the general population. Odds for cytopenias were assessed using logistic regression analyses adjusted for age, sex, ethnicity, hs-CRP, smoking, and alcohol use. Potential transplant-related risk factors were assessed in liver transplant recipients only. The median time since transplantation was 7.8 years, and 47% had autoimmune liver disease as the indication for transplantation. Compared to controls, liver transplant recipients had a higher prevalence of anemia (24.5% vs. 3.5%), neutropenia (2.1% vs. 0.1%), lymphocytopenia (18.4% vs. 1.5%), and thrombocytopenia (19.2% vs. 2.2%). Living with a transplanted liver was independently associated with higher odds of anemia (aOR, 7.84 [95% CI: 5.04 – 12.18], p<0.001), lymphocytopenia (aOR 16.69 [95% CI: 9.56 – 29.12], p<0.001), and thrombocytopenia (aOR 10.19 [95% CI: 6.07 – 17.13], p<0.001). No association was found between cytopenias, specific types of immunosuppressive treatments, or cirrhosis at transplantation. In conclusion, hematological abnormalities are common in liver transplant recipients, even several years post-transplantation, and increased attention towards cytopenia in this population is warranted.